(untitled) (African Journal of Dairy Farming and Milk Production, 2016)
The aim of the study was to determine the relative day-to-day variation in yield and composition of zebu cows. Ten multiparous zebu cows in day 41 ± 1.6 of lactation were used in the study. After a 14 day adaptation period, milk production was recorded daily for four consecutive weeks. Cows had access to natural pasture for 6.5 h per day and were also supplemented with hay, cottonseed cake and molasses. The cows were hand-milked and calves were used to stimulate milk ejection before and during milking. Average yield of saleable milk was 2.08 ± 0.23 l/day with a relative day-to-day variation of 18 -21%. The variation of saleable milk was 23 - 25% for fat, 12 - 14% for protein, 6% for lactose and 8% for somatic cell count. The variation in fat content was higher in strip milk (19 - 46%) than in saleable milk. The results indicated a larger variation in composition of milk from hand-milked Bos indicus Zebu than from machine-milked Bos taurus cows. The most likely reasons for the difference in variation are the suckling by the calf and that hand-milking entails larger variation in the degree of emptying machine-milking does.